Dihydroflavonol 4-Reductase Genes from Freesia hybrida Play Important and Partially Overlapping Roles in the Biosynthesis of Flavonoids - Li, Yueqing; Liu, Xingxue; Cai, Xinquan; Shan, Xiaotong; Gao, Ruifang; Yang, Song; Han, Taotao; Wang, Shucai; Wang, Li; Gao, Xiang (Frontiers in Plant Science, 2017)
Dihydroflavonol-4-reductase (DFR) is a key enzyme in the reduction of dihydroflavonols to leucoanthocyanidins in both anthocyanin biosynthesis and proanthocyanidin accumulation. In many plant species, it is encoded by a gene family, however, how the different copies evolve either to function in different tissues or at different times or to specialize in the use of different but related substrates needs to be further investigated, especially in monocot plants. In this study, a total of eight putative DFR-like genes were firstly cloned from Freesia hybrida. Phylogenetic analysis showed that they were classified into different branches, and FhDFR1, FhDFR2 and FhDFR3 were clustered into DFR subgroup, whereas others fell into the group with cinnamoyl-CoA reductase (CCR) proteins. Then, the functions of the three FhDFR genes were further characterized. Different spatio-temporal transcription patterns and levels were observed, indicating that the duplicated FhDFR genes might function divergently. After introducing them into Arabidopsis dfr (tt3-1) mutant plants, partial complementation of the loss of cyanidin derivative synthesis was observed, implying that FhDFRs could convert dihydroquercetin to leucocyanidin in planta. Biochemical assays also showed that FhDFR1, FhDFR2 and FhDFR3 could utilize dihydromyricetin to generate leucodelphinidin, while FhDFR2 could also catalyze the formation of leucocyanidin from dihydrocyanidin. On the contrary, neither transgenic nor biochemical analysis demonstrated that FhDFR proteins could reduce dihydrokaempferol to leucopelargonidin. These results were consistent with the freesia flower anthocyanin profiles, among which delphinidin derivatives were predominant, with minor quantities of cyanidin derivatives and undetectable pelargonidin derivatives. Thus, it can be deduced that substrate specificities of DFRs were the determinant for the categories of anthocyanins aglycons accumulated in F. hybrida. Furthermore, we also found that the divergence of the expression patterns for FhDFR genes might be controlled at transcriptional level, as the expression of FhDFR1/FhDFR2 and FhDFR3 was controlled by a potential MBW regulatory complex with different activation efficiencies. Therefore, it can be concluded that the DFR-like genes from F. hybrida have diverged during evolution to play partially overlapping roles in the flavonoid biosynthesis, and the results will contribute to the study of evolution of DFR gene families in angiosperms, especially for monocot plants.